Implementasi Metode Alif Dalam Meningkatkan Hasil Belajar Hafalan Al-Qur’an di TPQ A-Taqwa Wiyung Surabaya - Siti Fatimah Nur Rofiq Rofiq; Dr. Heryanto Susilo, S.Pd., M.Pd. (J+PLUS UNESA, 2026)
This study aims to describe the implementation of the Alif Method and analyze its supporting and inhibiting factors in improving students' Al-Qur'an memorization learning outcomes at TPQ At-Taqwa Wiyung Surabaya. This research uses a qualitative approach with a case study design. The research subjects consisted of three ustadzah and fifteen upper-level students selected through purposive sampling. Data collection was carried out through non-participatory observation for twelve sessions, in-depth interviews with the head of the TPQ and teachers, close-ended questionnaires for students, and documentation. Data analysis used an interactive model including data reduction, data display, and conclusion drawing. The results show that the implementation of the Alif Method using word-by-word repetition classically with a large numbered mushaf significantly improves students' memorization speed to one surah every two weeks. The main supporting factors are students' collective enthusiasm, a conducive mosque microsystem, and teacher competency. Meanwhile, the inhibiting factors are variations in students' initial reading abilities, limited afternoon duration (15–30 minutes), and student fatigue from full-day school. In conclusion, the Alif Method effectively enhances learning outcomes across cognitive, affective, and psychomotor domains simultaneously.